Implementasi Pelatihan Batik Shibori sebagai Upaya Pemberdayaan Perempuan melalui Pendidikan Luar Sekolah - Jordy Setiawan; Sumartini Sumartini; Supatmawati Supatmawati; Wardiani Ciptaningrum; Yuliati Yuliati (Jurnal Ilmiah Dan Karya Mahasiswa, 2026)
The implementation of Shibori batik making training for women's groups at Dea Modis Batik, Yogyakarta City, was motivated by the high amount of free time that housewives have not used productively and the low functional ability to develop their potential. This study aims to describe the implementation of Shibori batik training as an instrument for women's empowerment from the perspective of Non-Formal Education (PLS). The research approach used was descriptive qualitative. Data collection techniques included participatory observation of 10 learners, in-depth interviews with managers and instructors, and documentation studies, with the validity of the findings tested through triangulation techniques. The results showed that this training succeeded in fostering enthusiasm, commitment to learning, and honing the participants' motor skills in mastering various textile folding, tying, and color fixation techniques. In addition to increasing craft competency that produces aesthetic and adaptive motifs, this program was also effective in fostering awareness of online and local entrepreneurship. There was a positive psychological evolution in the form of increased self-confidence (self-efficacy) and a change in mental attitude from passive to proactive. The conclusion of the study confirms that the synergy of digital-based practical teaching has proven reliable in reconstructing the socio-economy of marginalized communities in an inclusive manner. This training successfully positioned the role of PLS ​​as an adaptive social safety net to build sustainable economic independence for women at the grassroots level.